The Role of Honour in Egils saga - Barreiro, Santiago Francisco (2016)
The aim of this text is to assess the role that honour plays in a long prose text composed in Iceland c.1220-1240, Egils saga Skalla-Grímssonar. First, we present the main theoretical and historiographical views on honour, both as a general concept and applied specifically to the Icelandic Middle-Ages. Furthermore, we analyze the vocabulary of honour present in the saga in order to identify figures in it which could have been considered as models of honourable behaviour. Finally, we discuss the notion of honour as a commodity and instead propose an alternative view. We hold that honour can be compared with the notion of inalienable wealth and exemplify our stance with a short case study of a scene in the saga.